1984
DOI: 10.1017/s0001566000007224
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parental Attitudes in the Development of Temperament in Twins at Home, School and in Test Situations

Abstract: In the La Trobe Twin Study, data are collected on temperament and social development in 3-15 year old twins and singletons from four different sources: questionnaires to parents covering development from birth to the present plus the Bristol Social Adjustment Guide completed by the teacher, Sattler's Behavior and Attitude Checklist completed by the tester, and the Qualitative Score on the Porteus Maze Test. Particular stresses are identified which the parents perceive as distinguishing a multiple from a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0
4

Year Published

1986
1986
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 19 publications
4
30
0
4
Order By: Relevance
“…In fact, only four mothers and six fathers exhibited Global Severity Index levels that were two standard deviations above the mean, a level indicative of clinical problems (Derogatis, 1992). The elevation of Global Severity Index levels relative to nonpatients is consistent with reports that parents express higher levels of psychological distress during the first few months following the birth of twins (Hay & O'Brien, 1984;Lytton, Singh, & Gallagher, 1995).…”
Section: Discussionsupporting
confidence: 87%
“…In fact, only four mothers and six fathers exhibited Global Severity Index levels that were two standard deviations above the mean, a level indicative of clinical problems (Derogatis, 1992). The elevation of Global Severity Index levels relative to nonpatients is consistent with reports that parents express higher levels of psychological distress during the first few months following the birth of twins (Hay & O'Brien, 1984;Lytton, Singh, & Gallagher, 1995).…”
Section: Discussionsupporting
confidence: 87%
“…For example. Hay and O'Brien (1984), employing a sample of over 200 twins, found that 2.4% of the twins were born weighing less than 1500 grams.…”
Section: Discussionmentioning
confidence: 99%
“…M oreover, no studi es are know n to us about the rel ati onshi p betw een the fami l y context on the one hand and the prenatal needs on the other. The avai l abl e studi es focus on the postnatal needs and concerns of parents, 12,[14][15][16][17] on the needs and concerns of a sel ect group of parents (for exampl e, cal l ers to a tel ephone hel pl i ne, parti ci pants i n a parent group, 1,18,19 ) or on onl y one speci fi c aspect of prenatal needs and concerns, such as pl anned practi cal hel p. 20 The fi ndi ngs of these studi es suggest that mothers are often not consci ous of the effect of twinship on their family. 9 We therefore undertook a more el aborate research project ai med at assessi ng the parenti ng experi ences, emoti ons, concerns and needs of (expectant) parents of tw i ns duri ng pregnancy and one year after the chi l dren's bi rth.…”
Section: Introductionmentioning
confidence: 99%